2013
DOI: 10.1016/j.mayocp.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine in the Secondary Prevention of Cardiovascular Disease: Systematic Review and Meta-analysis

Abstract: Compared with placebo or control, L-carnitine is associated with a 27% reduction in all-cause mortality, a 65% reduction in VAs, and a 40% reduction in anginal symptoms in patients experiencing an acute myocardial infarction. Further study with large randomized controlled trials of this inexpensive and safe therapy in the modern era is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0
18

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(137 citation statements)
references
References 24 publications
2
117
0
18
Order By: Relevance
“…In patients with chronic heart failure, the plasma carnitine levels are correlated with %FS, EF, and LVMI [24]. A meta-analysis also revealed that L-carnitine is associated with a 27 % reduction in all-cause mortality and a 40 % reduction in angina symptoms in patients experiencing acute myocardial infarction [25].…”
Section: Effects On Cardiac Parametersmentioning
confidence: 99%
“…In patients with chronic heart failure, the plasma carnitine levels are correlated with %FS, EF, and LVMI [24]. A meta-analysis also revealed that L-carnitine is associated with a 27 % reduction in all-cause mortality and a 40 % reduction in angina symptoms in patients experiencing acute myocardial infarction [25].…”
Section: Effects On Cardiac Parametersmentioning
confidence: 99%
“…19 The accumulations of mitochondrial long-chain acyl-CoA and long-chain acyl-carnitine have been shown to be reduced by Lcarnitine in ischemic hearts. 20 In a study designed by DiNicolantonio et al, 21 it was demonstrated that L-carnitine compared with placebo was associated with the reduction in all-cause mortality and ventricular arrhythmias (27% and 65%, respectively). Recently, NLR has been reported as a prognostic marker for atrial fibrillation after CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Q10 (25,26) and LC (46) have been used in different heart diseases for decades. Indeed, different mechanisms have been reported for the role of Q10 and LC in hs-CRP, IL-6, lipid profiles, and LVEF in various medical conditions.…”
Section: The Effect Of Q10 Plus Lc Supplementationmentioning
confidence: 99%
“…Myocardium tissue has one of the highest intracellular carnitine concentrations. It should be noted that myocardial carnitine levels are rapidly reduced during MI, and LC supplementation has been revealed to replace depleted myocardial carnitine levels, improve ejection fraction (48), and relieve angina symptoms (46). LC can also upturn mitochondrial transport of fatty acids and reduce availability for triglycerides synthesis that is effective in lipid profiles (24).…”
Section: The Effect Of Q10 Plus Lc Supplementationmentioning
confidence: 99%